PERBANDINGAN TEKNIK TREE SAMPLING DAN UNIT CONTOH LINGKARAN DALAM MENDUGA POTENSI TEGAKAN HUTAN TANAMAN EKALIPTUS (EUCALYPTUS PELLITA F. MEULL) - Ikhwan, Muhammad; Sadjati, Emy; Azwin, Azwin (Wahana Forestra: Jurnal Kehutanan, 2017)
The forest inventory is basically a data collection activities. This activity is relatively important, because the effect on further activities. Hence the data collected must have a high enough accuracy. A way of determining the sampling unit is considered to be simpler, easier, and faster is the tree sampling method. The purpose of this study was to quantify the potential large stands of eucalyptus in the Forest of eucalyptus plants in the Faculty of Forestry and calculate the relative efficiency of sample unit. The total area is 0.11 ha of eucalyptus stands. Unit examples used are circular, 4-trees sampling, sampling 5 -trees, and 6-trees sampling is done by simple random sampling method. Potential stands of eucalyptus with method 4 sample trees have an average volume stands perplot is 0.096 m3, with the volume of the stand for the entire area is 111.09 m3 with a sampling error of 43.65%. Potential stands of eucalyptus trees by the method of example 5 has a volume average stocking each plot is 0.091 m3, with the volume of the stand for the entire area is 105.40 m3 with a sampling error of 51%. Potential stands of eucalyptus by using 6 sample trees have an average volume stands each plot was 0.08 m3, with the volume of the stand for the entire area is 92.83 m3 with a sampling error o f 54.77%. Potential stands of eucalyptus with a diameter circular sample plots of 12 m has an average volume stands each plot is 6,37 m3, with the volume of the stand for the entire area is 65.61 m3 with a sampling error of 22.63%.